The Influence of Service Quality and Facilities on Customer Satisfaction and Loyalty of Blue Residence’s Boarding Room, West Jakarta - Kurnianingtyas, Chandra Dewi; Katrilia, Tiya; Bawono, Bawono (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2022)
Blue Residence Kos is a boarding house in West Jakarta. This business has been going on for a long time and and over time, the boarding house owner also needs to consider the potential risk of being lonely due to the loss of attractiveness of the boarding house. This business has a high customer turnover rate and many boarding rooms are found to be unoccupied. For this reason, it is necessary to control the quality of boarding services provided in services and facilities. This study examines the effect of service quality on customer satisfaction and loyalty boarding. It is proven that customer satisfaction and loyalty are influenced by service quality and boarding facilities. Customer satisfaction is affected by the variable boarding facilities and boarding services significantly and both variables affect simultaneously by 63.9%. Customer loyalty is not significantly affected by the variable costing facilities, but is significantly affected by the variable costing services. Simultaneously, customer loyalty is influenced by these two variables by 72.5%. Customer satisfaction regression formula Y1 = 1.379 + 0.423 X1 + 0.500 X2 and customer loyalty regression formula Y2 = -3.178 + 0.204 X1 + 0.775 X2. Researchers propose improvements with the QFD method and obtain a ranking of improvement priorities that have been evaluated for their level of competitiveness with competitors of the Blue Residence boarding house. Researchers also use quality management tools to control quality, namely Check Sheet, Pareto Diagram, and Fishbone.